2009
DOI: 10.1136/thx.2008.110239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of diagnostic methodology on the reported incidence of ventilator-associated pneumonia

Abstract: Background: The optimal method for diagnosing ventilator-associated pneumonia (VAP) is controversial and its effect on reported incidence uncertain. This study aimed to model the impact of using either endotracheal aspirate or bronchoalveolar lavage on the reported incidence of pneumonia and then to test effects suggested from theoretical modelling in clinical practice. Methods: A three-part single-centre study was undertaken. First, diagnostic performance of aspirate and lavage were compared using paired samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…Most of these studies have included patients with diverse pathologies (medical, surgical, trauma patients, etc), and this makes drawing conclusions difficult. In addition, the problem is further complicated by the different criteria and methods used to diagnose VAP, which in turn makes the comparison of results even more problematic [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have included patients with diverse pathologies (medical, surgical, trauma patients, etc), and this makes drawing conclusions difficult. In addition, the problem is further complicated by the different criteria and methods used to diagnose VAP, which in turn makes the comparison of results even more problematic [37].…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have suggested that publicly reported VAP rates may not accurately reflect clinical VAP. 20,21 However, a study of patients in our institution indicated that, while specific patients may differ, the rates of pneumonia were similar whether bronchoscopic or National Healthcare Safety Network criteria were used. 22 While this study was designed to be powered to detect a 50% reduction in the VAP rate, this was predicated on a historical VAP rate of 5.8 Ϯ 1.47 per 1,000 ventilator days, present in early 2010 during study planning.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the studies, the patients diagnosed by BAL had a lower number of confirmed VAP (6.1 vs. 25.5/1000 ventilation days) compared to those diagnosed with non-protective aspiration, which was characterised by 90% sensitivity and only 14% specificity [24]. The literature data indicate that VAP prophylaxis, in the form of the ventilation bundle, can result in notable effects, i.e., decreased incidence [3,15,23,25]; however, studies confirming the lack of infections of this type in a given period are sparse [17,26].…”
Section: Discussionmentioning
confidence: 99%